Proceso atención de enfermería gestante 12 semanas con anemia ferropenica. - Acosta Chagerben, Ely Damarys (2021)
Iron deficiency anemia is currently considered the most frequent type of anemia during the gestation period, it is characterized by the lack of healthy red blood cells which are important for the transport of appropriate oxygen to the body tissues, during the period of gestation it is essential to double the portion of iron, to produce a greater amount of blood and provide a greater portion of oxygen to the baby, some studies indicate that severe anemia in pregnancy is capable of considerably increasing the risk of premature babies, low weight at birth and postpartum depression. The interventions carried out were based on improving the state of the pregnant woman, thus avoiding fetal complications, by applying the taxonomies: Nursing Diagnosis (NANDA), Nursing Results Classification (NOC) and Nursing Interventions Classification (NIC), the objective of nursing care is to bring the patient and the product to the end of pregnancy.